PPP1R14B Is a Prognostic and Immunological Biomarker in Pan-Cancer - Deng, Mingxia; Peng, Long; Li, Jiamin; Liu, Xiong; Xia, Xichun; Li, Guangqiang (Frontiers in Genetics, 2021)
Recent studies showed that PPP1R14B was high expression in tumor tissue and patients with high expression of PPP1R14B had poor survival. However, the function and mechanisms of PPP1R14B in tumor progression remain ill defined. There was also no pan-cancer evidence for the relationship between PPP1R14B and various tumor types based on big clinical data. We used TCGA project and GEO databases to perform pan-cancer analysis of PPP1R14B, including expression differences, correlations between expression levels and survival, genetic alteration, immune infiltration, and relevant cellular pathways to investigate the functions and potential mechanisms of PPP1R14B in the pathogenesis or clinical prognosis of different cancers. Here in, we found that PPP1R14B was involved in the prognosis of pan-cancer and closely related to immune infiltration. Increased PPP1R14B expression correlated with poor prognosis and increased immune infiltration levels in DMSC. Our studies suggest PPP1R14B can be used as a prognostic biomarker for pan-cancer. Our findings may provide an anti-tumor strategy targeting PPP1R14B, including manipulation of tumor cell growth or tumor microenvironment, especially MDSC infiltration.